Germinação, vigor de sementes e crescimento de plantas de trigo (Triticum aestivum L.) submetidas a diferentes doses de pendimethalin - Zepka, Ana Paula dos Santos (2007)
The wheat is an important cereal in the feeding human being. One of the main problems of the culture is the control of harmful grass, many times carried through with the use of herbicides. With the objective to study the influence of different concentrations of the herbicide pendimethalin (zero, 50, 100, 150 and 200 mg i.a m-2) on wheat seeds, assays had been made in them will cultivate BRS 177, BRS 179 and Embrapa 40. The viability, the vigor of the seeds and the characteristics of growth of plants decrease with the increment in the dose of the product. To cultivate BRS 177 it was reached in such a way in the germination of the seeds how much in the emergency; already Embrapa 40, better presented performance in first test and BRS 179 in as. The electric condutivity increased in function of the increment in the concentration of pendimethalin in all to cultivate them, indicating loss of vigor. The development of the plants of cultivating BRS 179, that in the experiment they are not in competition with harmful grass, is affected negative by the herbicide, mainly in the two stronger doses: 150 and 200 mg i.a m-2. With these tests, it could be concluded that the herbicide pendimethalin induces the loss of the physiological quality of the seed and the growth of the plants of wheat of them to cultivate BRS 177, BRA 179 and Embrapa 40.